The Content Organization and Lexical-Stylistic Peculiarities of the Polish Diplomatic Documents Addressed to Ukraine (Released in December of 1991) (Linguostylistic Studies, 2020)
The article deals with the semantic structure and the most productive groups of the lexical stylistic devices that function in the Polish foreign diplomatic documentation addressed to the Ukrainian side in December, 1991, namely Statements of the Council of Ministers of the Republic of Poland (1991/12/02), Note from the Ministry of Foreign Affairs of the Republic of Poland (1991/12/27), Telegram of the President of the Republic of Poland Lech Wałęsa  (1991/12/3). The methods of typological (a study of the structure of diplomatic documents), descriptive (an analysis of the semantic content), functional (a research of the purpose of a note, a statement, a telegram), comparative (comparison of the language, graphical, and informative content of documentation) and linguistic analysis have been used to reveal the content organization of documents. All of them have common features, namely the text elements that contain logical information chains of the Ukrainian Independence recognition. However, they differ in some content aspects: the statement additionally informs about the issue of disarmament and military reduction; the telegram implies domination of the emotionally-expressive content which is verbally emphasized by the superlative form of the adjective; the note represents the first steps of the diplomatic relationship development such as the exchange of ambassadors. The study has revealed that the structure of all the official documents under the study is traditional for this functional style. Moreover, it includes the relevant appeals (the note, the telegram), complimentary forms of conclusion (the note), signature (the note, the statement, the telegram), information about the date and location the document creation (the note, the telegram). On the lexical level, all documents contain the elements of literary vocabulary that are emphasized by nouns, less frequently by adjectives, participles, verbs, adverbial participles, diplomatic terminology and cliches. They are used to provide the text accuracy, clarity, logic, conciseness, standardization, courtesy and highlight the value of the information, its credibility, and the relevance of the international law norms
Keywords: the diplomatic variety of the official business style,; the Polish diplomatic documentation,; the lexical-stylistic devices,; nomenclature names,; literary terms, cliches.